2016
DOI: 10.1080/19440049.2016.1184941
|View full text |Cite
|
Sign up to set email alerts
|

Non-targeted screening for contaminants in paper and board food-contact materials using effect-directed analysis and accurate mass spectrometry

Abstract: Due to large knowledge gaps in chemical composition and toxicological data for substances involved, paper and board food-contact materials (P&B FCM) have been emerging as a FCM type of particular concern for consumer safety. This study describes the development of a step-by-step strategy, including extraction, high-performance liquid chromatography (HPLC) fractionation, tentative identification of relevant substances and in vitro testing of selected tentatively identified substances. As a case study, we used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 28 publications
0
25
0
2
Order By: Relevance
“…Because the chemical constituents are not all known, chemical composition testing would be required as well as another round of toxicology assessments of the new individual chemical constituents. In a recent example, a chemical screen of a sample of a pizza box revealed many unidentifiable compounds-this demonstrates the uncertainty in content of even industrially produced products (Bengtström et al 2016). With this complexity in mind, we agree with John Warner, a strong advocate for product chemical safety, who recently laid out an argument for standard testing of finished products (Warner and Ludwig 2016).…”
Section: Print Use (Stage 5)mentioning
confidence: 87%
See 1 more Smart Citation
“…Because the chemical constituents are not all known, chemical composition testing would be required as well as another round of toxicology assessments of the new individual chemical constituents. In a recent example, a chemical screen of a sample of a pizza box revealed many unidentifiable compounds-this demonstrates the uncertainty in content of even industrially produced products (Bengtström et al 2016). With this complexity in mind, we agree with John Warner, a strong advocate for product chemical safety, who recently laid out an argument for standard testing of finished products (Warner and Ludwig 2016).…”
Section: Print Use (Stage 5)mentioning
confidence: 87%
“…In a recent example, a chemical screen of a sample of a pizza box revealed many unidentifiable compounds—this demonstrates the uncertainty in content of even industrially produced products (Bengtström et al. ). With this complexity in mind, we agree with John Warner, a strong advocate for product chemical safety, who recently laid out an argument for standard testing of finished products (Warner and Ludwig ).…”
Section: Methodsmentioning
confidence: 99%
“…We recently showed that quantifications could be decoupled from identification, and this allows for rough concentration estimates of virtually an unlimited amount of unidentified substances. Furthermore, studies by Bengtström et al and Rosenmai et al showed that untargeted screening can be used in a bio‐guided strategy to find hazardously compounds present in extracts from cardboard food packaging materials. This approach aims to avoid wasting effort identifying and quantifying irrelevant compounds by employing prioritization .…”
Section: Introductionmentioning
confidence: 99%
“…Yet, ideally elucidation, quantification, and prioritization should be performed on any present substance to assess which substances are risk relevant or risk irrelevant. It may be viable to adapt a strategy similar to recent literature and combine it with the latest semiquantification (SQ) approach to obtain a chemical exploration tool that can prioritize chemical substances based on adjustable endpoints.…”
Section: Introductionmentioning
confidence: 99%
“…A better way to understand a product's impact on human health and the environment is to test the final product. For example, one study that screened a sample of pizza box 6 revealed many unidentifiable compounds, raising questions about the content and safety of everyday products.…”
Section: Test Finished Productsmentioning
confidence: 99%